Legal Regulation of the Peculiarities of the Organization of Antiepizootic Measures in Specially Protected Natural Areas of Federal Significance - S. V. Gerasimov (Теоретическая и прикладная юриспруденция)
The article examines aspects of the legal regulation of the organization and implementation of veterinary preventive and antiepizootic measures in specially protected natural areas of federal signifi cance on the example of outbreaks of African swine fever in the state nature reserve “Mshinskoe swamp” of the Luga district of the Leningrad region in 2018–2019. An assessment of the current in the period 2018–2020 is given veterinary and environmental regulatory legal status of acts, with the revealed practical law enforcement collisions in the analyzed acts in the elimination of real outbreaks of African swine fever in the Leningrad region. The bureaucratic nature of the procedure for making decisions on the need to regulate the number of wild animals in specially protected natural areas of federal signifi cance and the practical implementation of these measures, revealed by practical law enforcement, was leveled by local rule-making of the Veterinary Directorate of the Leningrad Region, the legitimization of which was carried out by the actual elimination of infection in a reserve of federal signifi cance and the subsequent implementation of the developed regulation by the Ministry of Natural Resources resources and ecology of the Russian Federation into the system of quarantine measures. At the end of the article, substantiated proposals are formulated for amending the veterinary and environmental legislation in order to prevent the occurrence of the same legal collisions in the future and to promptly eliminate outbreaks of infectious diseases in the wild fauna, in particular in specially protected areas of federal signifi cance.